Financial Distress Analysis Using The Altman Z-Score, Zmijewski, Grover, Springate, And Ohlson Methods In Companies Listed In The Indonesian Sharia Stock Index For 2020-2023 - Ahmad Faisal Saputro; Ujang Syahrul Mubarrok (INVENTORY: JURNAL AKUNTANSI, 2025)
This study aims to determine the potential for bankruptcy using the Altman Z-Score, Zmijeski, Grover, Springate, Ohlson analysis methods in companies listed on the Indonesian Sharia Stock Index (ISSI) from 2020 to 2023. The method used in this research is descriptive quantitative, with 2 (two) analysis methods, namely descriptive methods and quantitative methods. Using descriptive methods, namely researchers will describe the results of calculations with sentences stating whether the company is in a healthy or unhealthy condition in terms of its finances. While quantitative methods are used to measure data in the form of numbers / numeric on financial statements. The population used for this study are pharmaceutical sub-sector consumer goods sector manufacturing companies listed on the Indonesian Sharia Stock Index for the period 2020 - 2023 with a total of 2 companies. The sampling technique in this study used the Purposive Sampling method. The results of this study show that financial analysis of PT Kimia Farma Tbk (KAEF) and PT Darya-Varia Laboratoria Tbk (DVLA) using various bankruptcy prediction models shows significant differences in the financial performance of the two companies. The Altman model indicated KAEF experienced a sharp Z-Score decline by 2023, underscoring the need for financial restructuring. In contrast, DVLA showed a stable performance with a Z-Score above 3.0, signaling a low risk of bankruptcy. The Zmijewski and Grover models note fluctuations in the financial health of KAEF, with an increased risk of bankruptcy in 2023. DVLA showed greater stability, despite some small declines in profitability and efficiency. The Springate and Ohlson models also reveal significant fluctuations in both companies, especially KAEF which faces major challenges in 2023. However, significant improvements in both companies were seen in various aspects, although DVLA overall showed stronger stability. The implications of the analysis using various models (Altman, Zmijewski, Grover, Springate, and Ohlson) show differences in financial health dynamics between PT Kimia Farma Tbk (KAEF) and PT Darya-Varia Laboratoria (DVLA) from 2020 to 2023. KAEF experienced a significant decline in 2023, with Z-Score and other models indicating an increased risk of bankruptcy, requiring financial restructuring and increased liquidity, debt reduction, and operational efficiency. Meanwhile, DVLA is performing well with low bankruptcy risk, despite a small decline in 2023. Although stable, DVLA needs to focus on profitability and liquidity to maintain its health in the future.